<u>Answer:</u>
Consistent and dependent
<u>Step-by-step explanation:</u>
We are given the following equation:
1. ![3x+6y-12z=36](https://tex.z-dn.net/?f=3x%2B6y-12z%3D36)
2. ![x+2y-4z=12](https://tex.z-dn.net/?f=x%2B2y-4z%3D12)
3. ![4x+8y-16z=48](https://tex.z-dn.net/?f=4x%2B8y-16z%3D48)
For equation 1 and 3, if we take out the common factor (3 and 4 respectively) out of it then we are left with
which is the same as the equation number 2.
There is at least one set of the values for the unknowns that satisfies every equation in the system and since there is one solution for each of these equations, this system of equations is consistent and dependent.
Answer:
24
Step-by-step explanation:
18 * 4 /3 = 72/3 = 24
Answer: Third Option
![x=1.469743](https://tex.z-dn.net/?f=x%3D1.469743)
Step-by-step explanation:
We have the following exponential equation
![3^{x+1}=15](https://tex.z-dn.net/?f=3%5E%7Bx%2B1%7D%3D15)
We must solve the equation for the variable x
To clear the variable x apply the
function on both sides of the equation
![log_3(3^{x+1})=log_3(15)](https://tex.z-dn.net/?f=log_3%283%5E%7Bx%2B1%7D%29%3Dlog_3%2815%29)
Simplifying we get the following:
![x+1=log_3(15)](https://tex.z-dn.net/?f=x%2B1%3Dlog_3%2815%29)
To simplify the expression
we apply the base change property
![log_b(y)=\frac{log(y)}{log(b)}](https://tex.z-dn.net/?f=log_b%28y%29%3D%5Cfrac%7Blog%28y%29%7D%7Blog%28b%29%7D)
This means that:
![log_3 (15)=\frac{log(15)}{log(3)}](https://tex.z-dn.net/?f=log_3%20%2815%29%3D%5Cfrac%7Blog%2815%29%7D%7Blog%283%29%7D)
Then:
![x+1=\frac{log(15)}{log(3)}](https://tex.z-dn.net/?f=x%2B1%3D%5Cfrac%7Blog%2815%29%7D%7Blog%283%29%7D)
![x=\frac{log(15)}{log(3)}-1](https://tex.z-dn.net/?f=x%3D%5Cfrac%7Blog%2815%29%7D%7Blog%283%29%7D-1)
![x=1.469743](https://tex.z-dn.net/?f=x%3D1.469743)
Answer:
product
Step-by-step explanation:
hope it helps
Answer:
tghghgkk
Step-by-step explanation: